The effectiveness of the combination of schema therapy and imago therapy on personal growth and couples’ communication instability - Mahmoudimozafar , Majid (Applied Family Therapy Journal (AFTJ), 2023)
Aim: Marriage can be stable or unstable according to various factors, including interpersonal problems of the couple. The aim of the research was to determine the effectiveness of the premarital counseling package training based on the integration of schema therapy and imagotherapy approaches on the treatment of interpersonal problems of couples on the verge of marriage. Research method: Method: The research was a semi-experimental method with a pre-test, post-test and two-month follow-up plan with the control group. The statistical population consisted of boys and girls on the verge of marriage who referred to Rah Farda Counseling Center in Tehran in 2021, and twenty couples were selected by random sampling. Then they were randomly divided into two groups consisting of 10 test pairs and 10 control pairs. For both groups, pre-test, post-test and follow-up were performed. Interpersonal problems questionnaire (Hurwitz et al., 1989) was used. The counseling package was conducted in eight ninety-minute sessions twice a week only for the experimental group. Data analysis was done using repeated measures analysis of variance and LSD post hoc test in SPSS version 22 software. The significance level of statistical tests was considered 0.05. Results: The results showed that the main effect of time (p = 0.006), the main effect of group (p = 0.001) and the interaction effect of time and group (p = 0.001) were significant on the variable of interpersonal problems. In the experimental group, the average pre-test scores of the couple’s interpersonal problems variable were significantly higher than the average scores of the post-test (p = 0.015) and follow-up (p = 0.024). In addition, there was no significant difference between the mean scores of the mentioned variable between the post-test and follow-up stages (p = 0.228), which means that the effect of the intervention of trainings is lasting over time in the experimental group. Conclusion: Based on the results, pre-marriage counseling package based on the integration of approaches and concepts of schema therapy and imagotherapy is effective in reducing the interpersonal problems of couples on the eve of marriage.